Differential effects of two probiotics on the risks of eczema and atopy associated with single nucleotide polymorphisms to Toll‐like receptors. Issue 3 (May 2015) - Marlow, Gareth; Han, Dug Yeo; Wickens, Kristin; Stanley, Thorsten; Crane, Julian; Mitchell, Edwin A.; Dekker, James; Barthow, Christine; Fitzharris, Penny; Ferguson, Lynnette R.; Morgan, Angharad R.
Abstract: Background: There is strong evidence to support a genetic predisposition to eczema and more recently studies have suggested that probiotics might be used to prevent eczema by modifying the expression of putative allergy‐associated genes. The aim of this present study was to investigate whether two probiotics, Lactobacillus rhamnosus HN001 (HN001) and Bifidobacterium animalis subsp. lactis HN019 (HN019), can modify the known genetic predisposition to eczema conferred by genetic variation in the Toll‐like receptor (TLR) genes in a high‐risk infant population. Methods: We selected 54 SNPs in the Toll‐like receptor genes. These SNPs were analysed in 331 children of sole European ancestry as part of a double‐blind, randomized, placebo‐controlled trial examining the effects of HN001 and HN019 supplementation on eczema development and atopic sensitization. Results: The data showed that 26 TLR SNPs interacted with HN001 resulting in a significantly reduced risk of eczema, 18 for eczema severity as defined by SCORAD ≥10 and 20 for atopic sensitization compared to placebo. There were only two SNPs that interacted with HN019 resulting in a reduced risk of eczema, eczema severity or atopy. Conclusions: This is the first study to show that the negative impact of specific TLR genotypes may be positively affected by probiotic supplementation. HN001 exhibits a much stronger effect than HN019 in this respect.